Pengembangan Model SMART dalam PjBL untuk Meningkatkan Kemandirian Belajar Mahasiswa pada Mata Kuliah Akhlakul Karimah - Rendy Yudha Pratama; Amir Syaifurrohman; Desi Permata Sari (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The low level of students’ learning autonomy in project-based courses, including Akhlakul Karimah Course, remains a challenge in higher education in the 21st century, which requires self-directed learning skills, responsibility, and the ability to manage research independently. This study aims to develop and examine the effectiveness of the SMART (Self-Managed Active Research Task) learning model within the framework of Project-Based Learning (PjBL) to enhance students’ learning autonomy. The research employed a Research and Development (R&D) approach through several stages, namely needs analysis, model design, expert validation, limited trials, and evaluation. Data were collected using learning autonomy questionnaires, observations, interviews, tests, and students’ reflections, and analyzed both quantitatively (paired t-test, N-Gain) and qualitatively. The results revealed that the SMART model obtained expert validation in the “very feasible” category (88.7%) and significantly improved students’ learning autonomy, with average scores increasing from 62.5 (pre-test) to 82.4 (post-test), accompanied by an N-Gain of 0.52 (moderate to high category) and p-value < 0.05. Students also responded positively to the model, showing improvements in initiative, responsibility, and self-confidence. Therefore, the SMART model within PjBL is proven effective in fostering learning autonomy while supporting 21st-century competencies. Prospectively, this model can be adapted to other courses and broader educational levels, supported by digital technology integration to strengthen its effectiveness.